PRINSIP KOMUNIKASI DALAM AL-QUR’AN UNTUK PROSES BIMBINGAN PRA-NIKAH - Afrizal Afrizal (SINTESA: Jurnal Kajian Islam dan Sosial Keagamaan, 2020)
Pre-Marriage Guidance is held in order to prepare the bride and groom, both in terms of physical or psychological to improve the welfare and strength of the family, the Government of Indonesia formulates legislation that complicates divorce and forms a marriage counseling body or better known as BP4. The Office of Religious Affairs (KUA), as the organizer, includes a bride-to-be course (Suscatin) as one of the requirements for the marriage registration procedure. Although the Koran does not specifically address the issue of communication, however, if examined there are many verses that provide a general description of the principles of communication. The Koran offers several communication principles that can be taken for the process of pre-marital guidance for prospective brides, namely the principle of Qaulan Baligha (قَوْلًا بَلِيغًا), Principles Qaulan Karima (قَوْلًا كَرِيمًا), Principles Qaulan Maysura (قَوْلًا مَيْسُورًا), Principles Qaulan Ma'rufa (قَوْلًا مَعْرُوفًا), Principles Qaulan Layyina (قَوْلًا لَيِّنًا), Principles Qaulan Sadidan (قَوْلًا سَدِيدً)